2018
DOI: 10.1093/hropen/hoy012
|View full text |Cite
|
Sign up to set email alerts
|

Peripartum and postpartum outcomes in uncomplicated term pregnancy following ART: a retrospective cohort study from two Italian obstetric units

Abstract: STUDY QUESTION Do singleton uncomplicated term pregnancies conceived by assisted reproductive technology (ART) have adverse peripartum and postpartum outcomes? SUMMARY ANSWER Term pregnancies following ART, even if uncomplicated until birth, have a higher risk of retained placenta and postpartum hemorrhage (PPH). WHAT IS KNOWN ALREADY There is consistent evidence that pregnancies following ART have higher incidence of complications during pre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
14
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 18 publications
(24 citation statements)
references
References 26 publications
(35 reference statements)
3
14
1
Order By: Relevance
“…Interestingly, there were no signi cant differences in neonatal outcomes between IVF and spontaneous conception in the male infertility subgroup. Vannuccini S found that in uncomplicated term pregnancies following ART, infants born after ART had similar birthweights, Apgar scores and arterial blood pH values as those of spontaneously conceived infants [43]. These ndings might indicate that the factors associated with infertility are more likely to be associated with adverse neonatal complications rather than the ART procedure itself, which is consistent with a previous study [44].…”
Section: Summary Of Key Ndingssupporting
confidence: 77%
“…Interestingly, there were no signi cant differences in neonatal outcomes between IVF and spontaneous conception in the male infertility subgroup. Vannuccini S found that in uncomplicated term pregnancies following ART, infants born after ART had similar birthweights, Apgar scores and arterial blood pH values as those of spontaneously conceived infants [43]. These ndings might indicate that the factors associated with infertility are more likely to be associated with adverse neonatal complications rather than the ART procedure itself, which is consistent with a previous study [44].…”
Section: Summary Of Key Ndingssupporting
confidence: 77%
“…Pregnancies conceived with Assisted Reproductive Technologies have a significantly higher rate of placentation defects (OR 2.63, 95% CI 1.31–5.26) [ 18 ]. Jackson showed a higher risk for RP in ART pregnancies than spontaneous conceptions (2.7% vs 0%, p = 0.02) and a higher risk for ART gestations conceived through donor oocytes versus autologous oocytes (3.3% vs 1.6%) [ 23 ].…”
Section: Resultsmentioning
confidence: 99%
“…Interestingly, there were no significant differences in neonatal outcomes between IVF and spontaneous conception in the male infertility subgroup. Vannuccini S found that in uncomplicated term pregnancies following ART, infants born after ART had similar birthweights, Apgar scores and arterial blood pH values as those of spontaneously conceived infants [ 43 ]. These findings might indicate that the factors associated with infertility are more likely to be associated with adverse neonatal complications rather than the ART procedure itself, which is consistent with a previous study [ 44 ].…”
Section: Discussionmentioning
confidence: 99%